Pesantren Terpadu Sebagai Solusi Problematika Pendidikan Agama Islam di Era Globalisasi - Vialinda Siswati (Program Pascasarjana Universitas Ibrahimy, 2018)
This article discussed about pesantren-based Islamic integrated education with the concept of integrated learning. Pesantren became great expectations of Muslims in the globalization era. Disclosure of pesantren of accepting modernization is regarded as a turning point Muslim recovery from the downturn. Pesantren who developed a system of public schools and Madrasah Diniyah as supporting educational institutions, regarded as the right system to develop professionalism, knowledge and noble character.